Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12301-021-00222-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium content of diet on crystal formation in urine of patients with calcium oxalate stones: a randomized crossover clinical trial

Abstract: Background Patients with idiopathic calcium oxalate stones are advised to consume a low-oxalate diet to prevent recurrence. In this study, on patients with calcium oxalate stones we have attempted to determine the effect of calcium content of diet on the formation of calcium oxalate crystals in urine by in vitro supersaturation study of fresh postprandial urine samples and observing the morphology of the crystals formed using polarized optical microscopy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[ 29 ] analysed the correlations for calcium, magnesium, sodium, potassium, zinc and creatinine and found correlation coefficients ranging from 0.22 for creatinine to 0.64 for zinc. However, our study is the first comprehensive exploration in stone formers—who have been reported to have peculiar fasting, postprandial, and/or circadian patterns of urinary excretions compared with non-stone formers [ 30–32 ]—and we could also examine the differential value of spot urines obtained at different times of day.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] analysed the correlations for calcium, magnesium, sodium, potassium, zinc and creatinine and found correlation coefficients ranging from 0.22 for creatinine to 0.64 for zinc. However, our study is the first comprehensive exploration in stone formers—who have been reported to have peculiar fasting, postprandial, and/or circadian patterns of urinary excretions compared with non-stone formers [ 30–32 ]—and we could also examine the differential value of spot urines obtained at different times of day.…”
Section: Discussionmentioning
confidence: 99%